Judo 9+ injury prevention protocol (J9+IPP) on balance, strength, and anaerobic fitness in elite judokas: a one-group pretest-post-test, quasi-experimental trial - Rawat, N.; Agarwal, S.; Anwar, U. (Comparative Exercise Physiology, 2024)
Judoka, the judo athlete, is involved in, high-intensity intermittent combat sport, to defeat the opponent by reversing body momentum with speed and skill. Hence the judokas are susceptible to injuries. Specific training and physical conditioning help the judoka perform efficiently with minimal risk of injuries. The judo9+ injury prevention protocol consisting of sport-specific exercises focuses on minimising lower limb risk factors. The objective of the study was to investigate the effects of judo 9+ injury prevention protocol on strength, balance, and anaerobic fitness in elite judokas. A sample of 20 (male and female elite judokas) aged between 20-40 years, were recruited in the study based on selection criteria. After demographic and baseline evaluation, the judo9+ injury prevention protocol was administered to each participant for four weeks (2 sessions/week). Balance (SEBT), lower limb strength (VJHT), and anaerobic fitness (SJFT) scores were administered before the training began and after the completion of the training. Pre-post-training changes were compared using, using the paired t-test. All the outcome measures, SEBT, VJHT and SJFT demonstrated statistical significant changes (P<0.05) following four weeks of judo9+ injury prevention training. Larger effect sizes of 0.94 and 1.42 with >90% power were reported in VJHT and SJFT, respectively. There is sufficient evidence from this study to confirm that judo9+ injury prevention training significantly improves lower limb strength and anaerobic fitness among elite judokas following four weeks of judo9+ injury prevention training. However, balance improvement might require longer duration.